2019
DOI: 10.1108/rjta-02-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Segmenting Islamic fashion lifestyle on Indonesian woman

Abstract: Purpose This paper aims to identify the typology of fashion lifestyle that is relevant to predict the individual difference in evaluating Islamic fashion product. Design/methodology/approach The study involved female respondents aged above 16 years and wearing hijab. The sample of this research is 697 respondents from four big cities in Indonesia (Jakarta, Bandung, Surabaya and Malang) with the population in this study constituting 264 million Indonesian people. A random procedure with socio-demographic (sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 37 publications
(29 reference statements)
0
9
0
2
Order By: Relevance
“…Notwithstanding the proliferation of online Hijab sellers, studies examining aspects affecting shoppers’ behaviour on online Hijab purchases are sparse. A notable study conducted by Kartajaya et al , 2019 asserted that online Hijab shoppers pay attention to fashion lifestyles such as fashion leadership, brand consciousness, consumption motives and consumption orientation. Other studies found that important factors influencing buying decisions of Hijab e-commerce include celebrity endorsers (Aprilia and Hidayati, 2020), language features (Suryananda and Rivia Himmawati, 2018) and shopper’s loyalty (Herliana et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the proliferation of online Hijab sellers, studies examining aspects affecting shoppers’ behaviour on online Hijab purchases are sparse. A notable study conducted by Kartajaya et al , 2019 asserted that online Hijab shoppers pay attention to fashion lifestyles such as fashion leadership, brand consciousness, consumption motives and consumption orientation. Other studies found that important factors influencing buying decisions of Hijab e-commerce include celebrity endorsers (Aprilia and Hidayati, 2020), language features (Suryananda and Rivia Himmawati, 2018) and shopper’s loyalty (Herliana et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the prior studies implying the electronic innovativeness's significance (Juaneda-Ayensa et al, 2016) makes it essential to consider this determinant and evidence its validity for the particular case of modest wear online purchase. Lastly, as the study concentrates on the modest wear business, it appears vital to involve a factor such as fashion innovation in clarifying the purchase intent of modest wear online, as suggested by Hassan and Harun (2016) and Kartajaya et al (2019).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Namun kebanyakan studi lebih berfokus pada dampak gaya hidup, misalnya terhadap niat pembelian (Nora & Minarti, 2017;Park, 2018;Lee, 2019;Putri, 2019); kepuasan konsumen (Naim, Hamid, & Wahab, 2019), nilai konsumsi (Antonio & Astika, 2019); keputusan pembelian (Laksono & Iskandar, 2019). Studi berbeda dilakukan oleh Kartajaya et al (2019) yang melakukan clustering untuk mengidentifikasi tipologi gaya hidup fashion yang relevan untuk memprediksi perbedaan individu dalam mengevaluasi produk busana Islami. Melibatkan 697 responden dari empat kota besar di Indonesia (Jakarta, Bandung, Surabaya dan Malang) studi mereka menemukan bahwa ada 11 faktor dan 6 segmen untuk mengelompokkan responden gaya hidup mode Islam.…”
Section: Pendahuluanunclassified
“…Telihat bahwa penelitian tentang perilaku konsumen belum didokumentasikan secara komprehensif, terutama terkait dengan religiusitas dan perilaku konsumen (Agarwala, Mishra, & Singh, 2019). Penelitian ini berupaya untuk menguji hubungan religiusitas dengan gaya hidup sebagai kelanjutan dari studi Kartajaya et al (2019) yang lebih bertujuan untuk mengelompokkan responden. Religiusitas dalam agama Islam dijadikan sebagai salah satu dasar dalam tumbuh kembang seseorang.…”
Section: Pendahuluanunclassified